Far from a distraction: Plastic pollution and the planetary emergency. (August 2022) - Lavers, Jennifer L.; Bond, Alexander L.; Rolsky, Charles
Abstract: Pollution of the environment with plastics has garnered significant public attention, but the topic has also been the focus of controversy, including assertions that resources are better spent on other topics, such as global warming. Here, we argue that plastic pollution and climate change are fundamentally linked, from the extraction of fossil fuels to the production of plastics, and eventual disposal. We demonstrate how plastics research and funding currently lag significantly behind that of climate change and conclude by advocating for a more integrated approach to addressing pressing conservation issues in the time of a planetary emergency. Graphical abstract: Unlabelled Image Highlights: Plastics and climate are coupled through shared processes and chemical blueprint. Failure to recognize plastic pollution and climate change connections impedes mitigation. Research and funding into plastic pollution lags significantly behind climate change. Far from being a distraction, plastics research footprint is only 2.5 % that of climate change. Plastic pollution affects livelihoods, human rights, and is rooted in colonialism.